Citizen participation on the crossway: Direct democracy mechanisms in Ecuador, Peru, Argentina - Welp, Yanina (2008)
Through a comparative study of Argentina, Ecuador, Peru, this article argues that popular en- quiries, citizen initiative and recall of term of office would contribute either to enforce delega- tive democracy, that is, executive power prominence based on popular support and against the other powers of the state, or to increase quality of democracy by introducing citizens’ control mechanisms and participation in decision making.